Adaptive immunity to human coronaviruses is widespread but low in magnitude. Issue 3 (17th March 2021) - Tan, Hyon‐Xhi; Lee, Wen Shi; Wragg, Kathleen M; Nelson, Christina; Esterbauer, Robyn; Kelly, Hannah G; Amarasena, Thakshila; Jones, Robert; Starkey, Graham; Wang, Bao Zhong; Yoshino, Osamu; Tiang, Thomas; et al.
Abstract: Objectives: Endemic human coronaviruses (hCoVs) circulate worldwide but cause minimal mortality. Although seroconversion to hCoV is near ubiquitous during childhood, little is known about hCoV‐specific T‐cell memory in adults. Methods: We quantified CD4 T‐cell and antibody responses to hCoV spike antigens in 42 SARS‐CoV‐2‐uninfected individuals. Antigen‐specific memory T cells and circulating T follicular helper (cTFH) cells were identified using an activation‐induced marker assay and characterised for memory phenotype and chemokine receptor expression. Results: T‐cell responses were widespread within conventional memory and cTFH compartments but did not correlate with IgG titres. SARS‐CoV‐2 cross‐reactive T cells were observed in 48% of participants and correlated with HKU1 memory. hCoV‐specific T cells exhibited a CCR6 + central memory phenotype in the blood, but were enriched for frequency and CXCR3 expression in human lung‐draining lymph nodes. Conclusion: Overall, hCoV‐specific humoral and cellular memory are independently maintained, with a shared phenotype existing among coronavirus‐specific CD4 T cells. This understanding of endemic coronavirus immunity provides insight into the homeostatic maintenance of immune responses that are likely to be critical components of protection against SARS‐CoV‐2. Abstract : Adaptive immunity to human coronaviruses includes widespread, low‐level antibody and CD4 T‐cell responses, which are maintained independently. All hCoV‐specific and cross‐reactive SARS‐CoV‐2‐specific CD4 T‐cell responses share a common phenotypic and memory profile. hCoV‐specific CD4 T cells were substantially enriched in human lung‐draining lymph nodes compared with the circulation, suggesting a potential anatomical niche for maintenance of hCoV cellular memory.